Making the most of youth development: Evidence-based programs and the role of young people in research. Issue 1 (14th June 2017) - Seymour, Kathryn; Bull, Melissa; Homel, Ross; Wright, Paul
Abstract: There is a growing international emphasis on the use of research-based evidence to inform youth program policy, practice and funding priorities, and on involving young people as subjects and actors in gathering this evidence. Youth development organisations and programs increasingly are expected to engage in research that informs their program development and illustrates their effectiveness. Research partnerships that provide community access to external research expertise are one way by which youth organisations and programs can strengthen their internal research capacity. This article explores the youth-inclusive community–university partnership underpinning the Queensland Youth Development Research Project, and examines some of the multifaceted methodological and ethical dimensions of this approach across three dimensions of research: planning, doing and finishing. Successful youth-inclusive research requires paying attention to the diversity of challenges characteristic of youth research. These challenges, influenced by the complexity of child, young adult and older adult relationships, highlight the fundamental importance of understanding how power is expressed and mediated in youth research. Overall, the article argues that youth-inclusive research can be shaped to bring broader benefits to research, scholars, young people and the wider community beyond the aim of simply improving the research process itself.